Protecting People and Economies : Integrated Policy Responses to COVID-19 - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 pandemic has unleashed a global health emergency and an unprecedented economic crisis of historic magnitude. Governments facing this threat are in uncharted territory, but three policy priorities addressed in this note are clear. Disease containment is a first-order concern to combat the pandemic, and measures such as testing and tracing, coupled with isolating and treating the infected can bring first-order gains. The economic crisis requires a parallel and simultaneous effort to save jobs, protect income, and ensure access to services for vulnerable populations. As governments act to slow the pandemic and protect lives and livelihoods now, they will need to maintain macro stability, continue to build trust, and communicate clearly to avoid deeper downturns and social unrest. Looking forward, this crisis can be an opportunity to rethink policy to build back with stronger systems for people and economies.